Luther and Contemporary Preaching: Narrative and Anthropology - Lischer, Richard (Scottish journal of theology, 1983)
Exhaustive studies of Martin Luther's preaching are few, and for good reason. The persistence of his scribes has resulted in a corpus of more than 2,000 sermons — and a tangle of questions concerning their authenticity and integrity. His theological program was such that in matters of content he did not maintain a rigid distinction between treatise and sermon. Everything we have from Luther ‘preaches’. Complicating the picture are the various postils, which are usually identified as ‘sermons’. The postils were not intended to do more than set a standard for others; yet they probably were delivered verbatim from some pulpits, and in The German Mass Luther says they should be!